Two legume defense proteins suppress the mobility of nasopharyngeal carcinoma cells. (1st November 2016) - Dan, Xiuli; Ng, Tzi Bun
Abstract: A 16-kDa trypsin inhibitor was isolated from an edible legume using various chromatographic procedures. The protein was unadsorbed on Affi-gel blue gel but adsorbed on DEAE-Sepharose and Mono Q following which media the protein was subsequently subjected to gel filtration on Superdex 75 and a final 21-fold purification was achieved. This trypsin inhibitor showed remarkable pH and thermal stability. Its inhibitory activity was impaired in the presence of 1 mM dithiothreitol. The anti-proliferative and anti-mobility activities of this trypsin inhibitor and a hemagglutinin isolated from the same legume were tested on nasopharyngeal carcinoma cells. These two defense proteins demonstrated discrepant anti-proliferative efficacies that the hemagglutinin could greatly suppress the proliferation of nasopharyngeal carcinoma cells, while the trypsin inhibitor revealed a minor effect. However, these two proteins could both attenuate the mobility of nasopharyngeal carcinoma cells. The present study revealed the potential of applying plant defense proteins in cancer treatment.